Pemberdayaan Guru PAUD dalam Penulisan dan Penerbitan Buku Cerita Anak - Kholifatul Fauziah; Cahyo Setiadi Ramadhan (Universitas Muhammadiyah Semarang, 2022)
This community service program is aimed at (1) improving teacher skills in designing fiction scripts in the form of making children's story books, (2) increasing the positive reputation of the teacher education institution concerned through increasing teacher expertise, the work produced and related positive publications in the mass media, and (3) increasing the intellectual property owned by the teacher in question himself. The participants of this activity were PAUD KB KB teachers 'Aisyiyah Surya Melati, Brajan, Tamantirto, Kasihan, Bantul. Preliminary studies through observation showed that none of these family planning teachers had published children's stories even though they had been struggling with the world of children's education for a long time. Therefore, this program was designed in the form of training in writing children's stories as well as assistance in the publication of these stories. There are 20 participants. This empowerment resulted in an anthology of children's stories with ISBN entitled